PERAN PENGAWASAN SUPERVISOR DI DEPARTEMEN HOUSEKEEPINGHOTEL ROYAL DENAI BUKITTINGGI - Wahyuni, Desi; Silfeni, Silfeni; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2015)
The purpose in this research to describe the role of supervisionat housekeeping department Royal Denai Hotel Bukittinggi that have five indicators are: supervision of human resource, materials, equipment,standart operating procedure and work area. This type of researchisdescriptivewithquantitative and qualitative approaches. Data collection techniques performedbyusing interviews, documentationandquestionnaires. The results showedthat in generalthe role ofsupervisionsupervisorinthe housekeepingdepartmentHotelRoyalDenaiBukittinggiclassifiedinthe category quitewellwith theinterpretation of57,14%.Kata kunci: Supervisor, Pengawasan, Housekeeping, Hotel